Slipping Rib Syndrome in a Female Adult with Longstanding Intractable Upper Abdominal Pain - Noman Ahmed Jang Khan; Saba Waseem; Saad Ullah; Hassan Mehmood (Case Reports in Medicine)
Slipping rib syndrome is a rare cause of abdominal or lower chest pain that can remain undiagnosed for many years. Awareness among health care personnel of this rare but significant disorder is necessary for early recognition. Prompt treatment can avoid unnecessary testing, radiographic exposure, and years of debilitating pain. A 52-year-old female was evaluated for a 3-year history of recurrent abdominal and lower chest pain. Pain was sharp, primarily located in the lower chest and subcostal region left more than right, waxing and waning, nonradiating, and aggravates with specific movements. She underwent frequent physical therapies, treated with multiple muscle relaxants and analgesics with minimal improvement. Imaging modalities including CT scan, MRI, and X-rays performed on multiple occasions failed to signify any underlying abnormality. Complete physical examination was unremarkable except for positive hooking maneuver. Dynamic flow ultrasound of lower chest was performed which showed slipping of the lowest rib over the next lowest rib bilaterally left worse than right, findings consistent with slipping rib syndrome. Slipping rib syndrome is caused by hypermobility of the floating ribs (8 to 12) which are not connected to the sternum but attached to each other with ligaments. Diagnosis is mostly clinical, and radiographic tests are rarely necessary. Hooking maneuver is a simple clinical test to reproduce pain and can aid in the diagnosis. Reassurance and avoiding postures that worsen pain are usually helpful. In refractory cases, nerve block and surgical intervention may be required.